PENGARUH RASIO LARUTAN PENCUCI PADA BAGIAN DADA DAN PAHA AYAM TERHADAP KARAKTERISTIK SURIMI BASED PRODUCT AYAM BROILER - Kurniawan, Mario; Matoetina, Maria; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2013)
Surimi-based product can be made from white meat like fish meat but also chicken meat which had different physicochemical properties, similar to if using different part of meat like breast and thigh. The study used Nested Factorial with the the factor is Ratio of Washing NaCl (P) consisted of 1:2 (P1). 1:3 (P2), 1:4(P3) which is nested in Chicken Meat Part Breast (D) and Thigh (P) done using 4 replication in Randomized Sample. The parameter are Gel quality (Gel strenght and Folding test), WHC, water content, and thaw drip surimi based product. Effects of factor were analyzed using ANOVA at Î± = 0.05, continued with DMRT at Î± = 0.05 for the significant parameter. The results showed that the Ratio of Washing Solution NaCl gave significant effect on all parameters studies in each Meats Part Nest. For Breast Part Nest: Increasing of Washing Solution Ratio significantly increased the WHC of surimi based product after thawing from 44,55% to 51,80%, WHC boiled surimi based product from 62, 51% to 69,09%, water content of surimi based product after thawing from 5,50% to 80,71%, gel strength from 2.642.674 g/s to 3.282, 874 g/s, folding test from 6.034,706 g/s to 21.113,346 g/s. For Thigh Part Nest: Increasing of Washing Solution Ratio significantly increased the WHC of surimi based product after thawing from 39,41% to 44,29%, WHC of boiled surimi based product from 56,43% to 63,39%, water content of surimi based product after thawing from 1,53% to 75,50%, gel strength from 1.942,890 g/s to 1.355,189 g/s, folding test from 0.130,079 g/s, to 14.807,769 g/s. Graphic of folding test showed that increasing of washing solution ratio increased gel elasticity properties from 1;2, 1:3, 1:4 on each meat part.